1991
DOI: 10.1002/1097-0142(19910201)67:3<550::aid-cncr2820670303>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of intermediate‐dose methotrexate and cytosine arabinoside, “Spread‐out” or “Up‐front,” in continuation therapy for childhood non‐T, non‐B acute lymphoblastic leukemia a pediatric oncology group study

Abstract: One hundred six children with newly diagnosed non-T-, non-B-cell acute lymphoblastic leukemia (ALL) were treated in a Pediatric Oncology Group (POG) pilot study in which six courses of intermediate-dose methotrexate (MTX) and cytosine arabinoside (Ara-C) (1 g/m2 each) were added to a "backbone" of standard continuation therapy. The dose and sequence of MTX/Ara-C administration were based on a preclinical model that demonstrated synergism between MTX and Ara-C. Poor-risk patients (n = 49) were assigned to "up-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The rate of toxicity is similar to that previously seen with HDMTX/cytarabine regimens in front-line therapy trials for ALL patients. [17][18][19][20] Because we have previously shown that delayed methotrexate excretion at approximately 44 h is more likely among patients with poor clearance during the 24 h infusion, it is possible that delayed excretion and therefore toxicity was minimized with this targeting strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of toxicity is similar to that previously seen with HDMTX/cytarabine regimens in front-line therapy trials for ALL patients. [17][18][19][20] Because we have previously shown that delayed methotrexate excretion at approximately 44 h is more likely among patients with poor clearance during the 24 h infusion, it is possible that delayed excretion and therefore toxicity was minimized with this targeting strategy.…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9][10][16][17][18] The Pediatric Oncology Group in 1986 opened a randomized study to evaluate if the addition of either intensive ASP or AraC to IDMTX intensification would enhance the survival of children with ALL. The study intentionally used only antimetabolite therapy in order to decrease the long-term effects that are associated with ther- Toxicity grading: infection − 3 = treatment required, 4 = life-threatening; nausea/vomiting -3 = vomiting 1-4/day, 4 = hydration required; stomatitis -3 = ulcers, unable to eat, 4 = massive ulcer; CNS -3 = seizures, psychosis, 4 = comatose.…”
Section: Discussionmentioning
confidence: 99%
“…The Pediatric Oncology Group (POG) performed a pilot study using overlapping 24-h infusions of the anti-metabolite methotrexate (MTX) and cytarabine (AraC) for intensification therapy. 7 At 4 years, the Kaplan-Meier estimate of event-free survival (EFS) was 71 ± 7% for 57 standard prognosis patients and 53 ± 8% for Correspondence: MB Harris, Tomorrows Children's Institute, Hackensack University Medical Center, 30 Prospect Avenue, Hackensack, NJ 07601, USA; Fax: 201-487-7340 49 high-risk patients. Clavell and colleagues 8 reported that a regimen including intensive weekly intramuscular (i.m.)…”
Section: Introductionmentioning
confidence: 99%
“…However, a subsequent comparative study by the Paediatric Oncology Group (POG) revealed that a three drug combination of methotrexate, hydrocortisone, and cytarabine, injected intrathecally during remission induction and periodically during the next 2 years of continuation chemotherapy, was therapeutically equivalent to cranial irradiation and intrathecal methotrexate (Sullivan, et al, 1982). In a recent POG pilot study in which intermediate high dose methotrexate and cytarabine were administered as well as three drug intrathecal therapy, only three of 99 patients developed primary meningeal relapse (Krance et al, 1991). In the last 5 years of experience at M.D.…”
Section: Discarding Preventive Meningeal Irradiationmentioning
confidence: 99%
“…Non-comparative studies of ALL have been described in which better remission experience is claimed for use of multiple drugs, including anthracyclines and alkylating agents, rather than simpler antimetabolite regimens (reviewed by Rivera & Mauer, 1987 (Camitta et al, 1989;Land et al, 1989;Krance et al, 1991). These studies have yielded therapeutic results historically comparable to those of the more extensive multiple drug regimens, but without the liability of their potential adverse sequelae.…”
Section: The Limits Of Intensification Of Treatmentmentioning
confidence: 99%